EDUKASI PRODUCT KNOWLEDGE DALAM MENINGKATKAN LOYALITAS PELANGGAN WISATA SUSUR SUNGAI DI KERENG BANGKIRAI, KALIMANTAN TENGAH - Peridawaty, Peridawaty; Toendan, Rita Yuanita; Tunjang, Hansly (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to increase the loyalty of customers of riverside tourism in the Kereng Bangkirai area, Central Kalimantan, through product knowledge education to tourism managers and business actors. The main problem faced is the low understanding of guides and business actors towards information on tourism products, the potential of ecotourism, and the educational value that can be conveyed to tourists. The implementation method uses a participatory approach through socialization, training, service simulation, and direct mentoring. The results of the activity show an increase in tourism actors' understanding of product knowledge, an improvement in the quality of information services to tourists, and the emergence of a tendency to increase customer satisfaction and loyalty. This activity proves that product knowledge education is an important factor in building a meaningful travel experience and encouraging customer loyalty in a sustainable manner.